Antibiotic use in poultry farming: a cross-sectional study of veterinary practices in Tunisia - Ben Ali, Mehdi; Chtioui, Badi; Bouchrit, Hamza; Laamiri, Hatem; Attia El Hili, Hedia (Frontiers in Antibiotics, 2025)
Antimicrobial resistance (AMR) in poultry production poses a growing public health threat due to the emergence of multidrug-resistant (MDR) bacteria and the risk of transmission to humans through direct or indirect contact with these germs. In Tunisia, limited data on antibiotic use and veterinary prescribing practices hinder the development of effective AMR mitigation strategies, particularly in a sector with high antibiotic consumption. A cross-sectional study was conducted among veterinarian prescribers in avian medicine in Tunisia to assess their antibiotic prescribing behaviours and related practices and to evaluate their potential contribution to AMR emergence and spread. The most frequently reported first and second-line antibiotics were enrofloxacin (20/52 and 14/52), florfenicol (14/52 and 14/52), and doxycycline (7/52 and 6/52). Colistin (10/52) was the most used third-line antibiotic. These antibiotics were often administered without microbiological confirmation. Although 69% had access to accredited labs, 42% relied on rapid antimicrobial susceptibility tests (RASTs). Waste management practices were inadequate, with 50% disposing of biological waste in regular trash and 42% discarding expired antibiotics into the environment. Additionally, 77% reported frequent farmer self-medication. These findings highlight the urgent need for targeted training, improved surveillance, and the application of the One Health approach to tackle AMR in Tunisia’s poultry sector.